Impact of a Fermented High-Fiber Rye Diet on Helicobacter pylori and Cardio-Metabolic Risk Factors: A Randomized Controlled Trial Among Helicobacter pylori-Positive Chinese Adults - Xue, Kun; Liu, Yuwei; Iversen, Kia Nøhr; Mazidi, Mohsen; Qu, Zheng; Dong, Chenglin; Jin, Tayi; Hallmans, Göran; Åman, Per; Johansson, Anders; He, Gengsheng; Landberg, Rikard (Frontiers in Nutrition, 2021)
Background: High dietary fiber intake has been associated with reduced risk of Helicobacter pylori infection and co-morbidities such as gastric cancer but also with reduced risk of cardiovascular disease. It has been suggested that fermented rye could affect Helicobacter pylori bacterial load and that high- fiber rye may be superior to wheat for improvement of several cardiometabolic risk factors, but few long-term interventions with high fiber rye foods have been conducted. Objective: To examine the effect of high-fiber wholegrain rye foods with added fermented rye bran vs refined wheat on Helicobacter pylori infection and cardiometabolic risk markers in a Chinese population with a low habitual consumption of high fiber cereal foods. Design: A parallel dietary intervention was set up and 182 normal- or overweight men and women were randomized to consume wholegrain rye products containing fermented rye bran (FRB) or refined wheat (RW) for 12 weeks. Anthropometric measurements, fasting blood sample collection and 13C-urea breath test (13C-UBT) were performed at baseline and after 6 and 12 weeks of intervention as well as 12 weeks after the end of the intervention. Results: No difference between diets on Helicobacter pylori bacterial load measured by 13C-UBT breath test or in virulence factors of Helicobacter pylori in blood samples were found. Low density lipoprotein cholesterol (LDL-C) and high sensitivity C-reactive protein (hs-CRP) were significantly lower in the FRB group, compared to the RW group after 12 weeks of intervention. The intervention diets did not affect markers of glucose metabolism or insulin sensitivity. Conclusions: While the results of the present study did not support any effect of FRB on Helicobacter pylori bacterial load, beneficial effects on LDL-C and hs-CRP were clearly shown. This suggest that consumption of high fiber rye foods instead of refined wheat could be one strategy for primary prevention of cardiovascular disease. Registered at www.clinicaltrials.gov (Identifier: NCT03103386).